The Doing business indicators and economic performance - SAIDHONOV, Saidislombek (KDI School, 2016)
There are a number of determinants of economic growth. However, the role of investment climate cannot be underestimated. The World Bank Group’s Doing Business Reports can be a good proxy to measure the business climate of each country. More and more countries have been using the Doing Business Index to conduct reforms for amendment of business environment within countries. The outcome of this paper assists in prioritizing the reforms and suggesting different views maximizing the efficiency of reforms. The empirical evidence of the paper suggests that the index has the impact in the case of developing countries and emphasizing on ‘Enforcing Contract’ and ‘Starting Business’ is more beneficial to improve the overall index. Thus, reformers should focus on the initial stages of the business cycle rather than on exit stages.
Thesis(Master) --KDI School:Master of Public Policy,2016